ANALISIS COST AND EFFECTIVITY PROGRAM KARTU PRAKERJA DI INDONESIA - Yasserina Rawie; Palupi Lindiasari Samputra (Departemen Administrasi Publik, Universitas Diponegoro, 2020)
This article discusses the feasibility of the Program Kartu Prakerja as a social security program in dealing with the problem of unemployment in Indonesia. As a form of social security program, Suharyadi et al (2015) stated that the pre-employment card program is possible to overcome the problem of unemployment and poverty in Indonesia. However, other research conducted by Shomad (2010) explains that social security cannot overcome poverty. An example is the Direct Cash Assistance (BLT) program in the era of former president Susilo Bambang Yudhoyono, who faced a number of obstacles in realizing social welfare. This research is a recommendation research as a procedure in the analysis of the Workers Card policy to see the feasibility of the program. This research uses a quantitative approach with cost and effective analysis. Cost and effectivity analysis is done by making a comparative picture related to the cost and effectiveness of Program Kartu Prakerja. Based on the results of the analysis of cost effectiveness in this study, it was found that the most effective was alternative 2 (ratio 15: Rp. 11,207,402,000,000), namely only by providing training to the unemployed. Therefore, based on the results of the analysis in this study, Program Kartu Prakerja is feasible, but there are things that need to be reconsidered, namely the provision of incentives for the unemployed.